2010
DOI: 10.1172/jci36666
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of emphysema in mice through lentiviral transduction of long-lived pulmonary alveolar macrophages

Abstract: Directed gene transfer into specific cell lineages in vivo is an attractive approach for both modulating gene expression and correcting inherited mutations such as emphysema caused by human α1 antitrypsin (hAAT) deficiency. However, somatic tissues are mainly comprised of heterogeneous, differentiated cell lineages that can be short lived and difficult to specifically transfect. Here, we describe an intratracheally instilled lentiviral system able to deliver genes selectively to as many as 70% of alveolar macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 62 publications
(83 reference statements)
3
66
2
Order By: Relevance
“…Secondly, in Malawian adults we found that AM carbon tracks closely with the BC-generating potential of the fuel regularly used in the home for cooking [30]. Thirdly, the lifespan of AM in the lower airway, and therefore its ability to acquire inhaled BC, is up to several months [31]. A further limitation is that there was a sex imbalance between cyclists and non-cyclists in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…Secondly, in Malawian adults we found that AM carbon tracks closely with the BC-generating potential of the fuel regularly used in the home for cooking [30]. Thirdly, the lifespan of AM in the lower airway, and therefore its ability to acquire inhaled BC, is up to several months [31]. A further limitation is that there was a sex imbalance between cyclists and non-cyclists in the present study.…”
Section: Discussioncontrasting
confidence: 55%
“…In contrast, PBAE-CPs transfected only 3% of total cells, similar to previous findings with other leading nonviral (45-47) and viral (48,49) vectors. PBAE-MPPs demonstrated transgene expression in 12% of the CD45-negative nonimmune cells in the mouse lung, in contrast to the predominant transduction of immune cells achieved by viral vectors (50). Of note, the nonimmune cells in the lung lumen include airway epithelial cells, which comprise less than 1% of the total respiratory epithelial surfaces (51), as well as alveolar epithelial cells types I and II, which constitute 8% and 15% of the total peripheral lung cells, respectively (52,53).…”
Section: Resultsmentioning
confidence: 77%
“…At least two previous studies have shown that lentiviral vectormediated transduction of mouse lung leads to persistent (15 and 24 mo) gene expression in the murine lower airways (18,19). However, both studies used a VSV-G-pseudotyped lentiviral vector, which almost exclusively transduces alveolar macrophages, rather than lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%